Evaluating trauma center structural performance: The experience of a Canadian provincial trauma system - Moore, Lynne (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Indicators of structure, process, and outcome are required to evaluate the performance of trauma centers to improve the quality and efficiency of care. While periodic external accreditation visits are part of most trauma systems, a quantitative indicator of structural performance has yet to be proposed. The objective of this study was to develop and validate a trauma center structural performance indicator using accreditation report data. MATERIALS AND METHODS: Analyses were based on accreditation reports completed during on-site visits in the Quebec trauma system (1994-2005). Qualitative report data was retrospectively transposed onto an evaluation grid and the weighted average of grid items was used to quantify performance. The indicator of structural performance was evaluated in terms of test-retest reliability (kappa statistic), discrimination between centers (coefficient of variation), content validity (correlation with accreditation decision, designation level, and patient volume) and forecasting (correlation between visits performed in 1994-1999 and 1998-2005). RESULTS: Kappa statistics were >0.8 for 66 of the 73 (90%) grid items. Mean structural performance score over 59 trauma centers was 47.4 (95% CI: 43.6-51.1). Two centers were flagged as outliers and the coefficient of variation was 31.2% (95% CI: 25.5% to 37.6%), showing good discrimination. Correlation coefficients of associations with accreditation decision, designation level, and volume were all statistically significant (r = 0.61, -0.40, and 0.24, respectively). No correlation was observed over time (r = 0.03). CONCLUSION: This study demonstrates the feasibility of quantifying trauma center structural performance using accreditation reports. The proposed performance indicator shows good test-retest reliability, between-center discrimination, and construct validity. The observed variability in structural performance across centers and over-time underlines the importance of evaluating structural performance in trauma systems at regular intervals to drive quality improvement efforts.